The role of experience in problem solving and innovative tool use in crows - von Bayem, A; Heathcote, R; Rutz, C; Kacelnik, A (Elsevier, 2009)
Creative problem solving and innovative tool use in animals are often seen as indicators of advanced intelligence because they seem to imply causal reasoning abilities. However, complex behavior can also arise from relatively simple mechanisms, and the cognitive operations underlying seemingly "insightful" behavior are rarely examined. By controlling and varying prior experience, it is possible to determine the minimum information animals require to solve a given problem. We investigated how pretesting experience affects the performance of New Caledonian crows (Corvus moneduloides) when facing a novel problem. The task (developed by Bird and Emery) required dropping stones into a vertical tube to collapse an out-of-reach platform in a transparent box and release a food reward. After establishing that the birds had not preexisting tendency to drop stones into holes, subjects were assigned to two experimental groups that were given different kinds of experience with the affordances of the apparatus. Crows that had learned about the mechanism (collapsibility) of the platform without the use of stones passed the task, just like the subjects that had previously been trained to drop stones. This demonstrates that successful innovation was also possible after acquaintance with just the functional properties of the task.